Spanish video with english subtitles. In-situ monitoring system in the dry corridor of Guatemala through the establishment of a digital agricultural plot - Martínez Salgado, Jesús David; Jimenez Rodas, Daniel Ricardo; Arce Gomez, Daniela (2023)
In this video we highlight the Value-proposition Ag-plot testing of automated field in Guatemala , Situated in the region's challenging dry corridor, this innovative plot, supported by CGIAR, CUNORI University, and other partners, is designed to enhance decision-making and efficiency for small-scale farmers. It achieves this through advanced sensors and technologies that deliver precise data on climate and soil conditions. The plot functions as a laboratory, testing technologies that are apt for the unique challenges of the dry corridor, with a focus on social, environmental, and economic efficiency, while also addressing the needs of the regional community. Conducting user research is crucial, serving as a compass to guide our actions. This pioneering laboratory aims to optimize agri-food systems and expand the model, benefiting farmers in Guatemala and potentially in other countries, through the advancement of digital technology